PERAMALAN DATA INDEKS HARGA KONSUMEN KOTA PURWOKERTO MENGGUNAKAN MODEL FUNGSI TRANSFER MULTI INPUT - Inarotul Amani Rizki Ananda; Tarno Tarno; Sudarno Sudarno (Jurnal Gaussian, 2020)
The Consumer Price Index (CPI) provides information on changes in the average price of a group of fixed goods or services that are generally consumed by households within a certain period of time. The General CPI is formed from 7 sectors of public consumption expenditure groups. Because the formation of the consumer price index value is influenced by several sectors, the method that can be used is the transfer function method. The purpose of this study is to analyze the transfer function model so that the best model is produced to predict CPI in Purwokerto for the next several periods. In this study, general CPI modeling will be carried out based on the CPI value for the transportation services sector and the CPI for the Health sector in Purwokerto from January 2014 to July 2019 using the multi-input transfer function method. Based on the analysis, the best models are obtained, namely the multi-input transfer function model (2,0,0) (0,1,0) and the ARIMA noise series ([3], 0,0). The model has an Akaike's Information Criterion (AIC) value of 72.42021 and an sMAPE value of  2,351591 % which indicates that the model can be used for forecasting..Keywords: Consumer Price Index (CPI), Inflation,transfer function, AIC